Students' Perceptions of Using ChatGPT in English Learning at SMA Negeri 5 Pematangsiantar - Tampubolon, Sintia Enrika; Munthe, Melda Veby Ristella; Situmeang, Siska Anggita (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to determine the students' perceptions of using ChatGPT in English learning at SMA Negeri 5 Pematangsiantar. This research used a qualitative descriptive method. The population of this study consisted of class XI students, with a total of 36 participants selected through purposive sampling. The data were collected using a questionnaire and interview. The results of this study show that out of a total of 720 responses, 170 (22.28%) selected